THE IMPORTANCE OF SILVER RATIOS - Khursanoy Muminova (Web of Journals Publishing, 2024)
This scientific article is devoted to the study of the mathematical, scientific and practical significance of the silver ratios. The article, first of all, provides detailed information about the mathematical structure of the silver ratios and its historical development. The silver ratio is a quantity that expresses the ideal relationship between two numbers, and its specific properties are widely used in the fields of art, architecture, physics and biology. The article also pays special attention to the role of the silver ratio in creating geometric and aesthetic balance. This ratio is considered, in particular, as a necessary basis for understanding beauty, symmetry and order in nature and human activity.
Keywords: Silver ratio, chain fraction, positive irrational, symmetry, chord, aesthetics, engineering.